Analysis of the Territorial Aggressive Behavior of the Bioluminescent Flashlight Fish Photoblepharon steinitzi in the Red Sea - Hellinger, Jens; Jägers, Peter; Spoida, Katharina; Weiss, Linda C.; Mark, Melanie D.; Herlitze, Stefan (Frontiers in Marine Science, 2020)
The flashlight fish Photoblepharon steinitzi inhabit coral reef caves in the Red Sea. During the night they dwell alone or in pairs near their cave entrance, characteristic of territorial like behavior. A special feature of the flashlight fish is a bioluminescent organ located under their eyes, which emits blue green light. This bioluminescence may have various functions including intraspecific communication. To gain a better understanding of how these bioluminescent signals are used during territorial aggression, we investigated the territorial behavior of Photoblepharon steinitzi in its native environment. Using infrared video recordings at night, we found that Photoblepharon steinitzi increases its blinking frequency, while attacking intraspecific intruders, different artificial light organs or a fish dummy simulating an intraspecific intruder. All three stimuli presented to Photoblepharon steinitzi elicited four different types of attack modes (i.e. darting, border crossings, repetitive swimming toward stimuli and aggressive contact with stimuli such as ramming and bites) to varying degrees coupled with high blinking frequencies. These attacks occurred near the entrance of the cave where Photoblepharon steinitzi mainly resides during the night, suggesting a territorial behavior. Collectively our data show that flashlight fish Photoblepharon steinitzi changes its blinking pattern from low blink frequencies due to nearly constant open light organs to high blink frequencies during different modes of territorial aggression depending on the quality of the light stimulus and shape of the dummy.